2005
DOI: 10.1007/s00147-004-0694-7
|View full text |Cite
|
Sign up to set email alerts
|

The value of routine ophthalmological tests in the screening for lung transplantation

Abstract: We aimed to analyse the results of ophthalmological examinations in the screening before and in the follow-up after lung transplantation. Altogether, 295 consecutive patients who had undergone ophthalmological examination in the screening before lung transplantation were analysed. Preoperatively 27% ocular abnormalities were found; none of them formed a contraindication for the transplantation. Of the 122 patients who underwent transplantation, 24 (20%) had postoperative ocular complaints. We can conclude that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Additionally, none of the presumed "absolute contraindications" to transplantation, such as incidental ocular malignancy or asymptomatic intraocular infection, meet epidemiological screening criteria [3,8]. Our data are similar to published numbers by Sere et al, who also found no ocular contraindications to lung transplantation (0/295), resulting in a systematic change to the national Dutch lung transplant program that no longer requires inpatient ophthalmologic screening [9]. Therefore, we support a symptom-based approach to both pre-and post-transplant consultation in order to minimize harm through unnecessary exposures and potential medication side effects (e.g., phenylephrine-induced reflex bradycardia) [4,10].…”
supporting
confidence: 87%
“…Additionally, none of the presumed "absolute contraindications" to transplantation, such as incidental ocular malignancy or asymptomatic intraocular infection, meet epidemiological screening criteria [3,8]. Our data are similar to published numbers by Sere et al, who also found no ocular contraindications to lung transplantation (0/295), resulting in a systematic change to the national Dutch lung transplant program that no longer requires inpatient ophthalmologic screening [9]. Therefore, we support a symptom-based approach to both pre-and post-transplant consultation in order to minimize harm through unnecessary exposures and potential medication side effects (e.g., phenylephrine-induced reflex bradycardia) [4,10].…”
supporting
confidence: 87%
“… 12 Retrospective data from 295 patients found 0 ocular contraindications to lung transplantation in routine pretransplant examinations in this especially vulnerable, immunocompromised population. 13 These findings recently were replicated. 14 …”
mentioning
confidence: 80%